Perception and Implementation of Sports Safety Measures Among University Physical Education Instructors in Punjab: A Cross-Sectional Study - Atul Khajuria; Christian Gendemeh; Stephen Monday; Samuel Kamanda (Recent Trends in Sports, 2025)
Introduction: Considerable attention must be focused on sports safety as it is a constituent of thephysical education (PE) curriculum at the university level, in view of the frequent and vigorous engagement in physical activities. While there is general acknowledgement of the existence of safetymeasures, the extent to which such measures are put into practice may differ. This research examines the perceptions and practices related to sports safety of university PE teachers in Punjab, India, for identifying gaps between knowledge and practice, and investigating reasons for effective implementation failures. Methodology: A descriptive cross-sectional survey design was used, consisting of 93 public and private university PE instructors from different regions of Punjab. Data were collected using a structured questionnaire, which was divided into four parts: demographics, perception of safety measures, implementation practices, and barriers. Statistical analysis was conducted using SPSS version 25, employing descriptive statistics and Pearson analysis. Results: This study determined that the majority of respondents accepted the importance of sports safety (M=4.4, SD=0.5), and 79% accepted that the existence of safety protocols reduces the possibility of sustaining injuries. However, only 56% of them indicated enough support from their institutions. Though 85% of the instructors conducted equipment checks, fewer performed regular risk assessments (56%) and the enforcement of protective gear use (45%). Inefficient funding (61%) and lack of training (48%), as well as inadequate assistance from the institution (42%), were the primary barriers. Discussion: The research identifies a discrepancy between a high level of awareness concerning sports safety and the inconsistent observance of safety measures. In this case, the gap is due to systemic problems such as insufficient funding and lack of enforcement policies. The results are consistent with earlier studies, which suggest that logistical and institutional difficulties hinder effective safety management in educational facilities. Conclusion: Logically, physical education teachers in Punjab understand the value of sports safety; however, they are unable to execute proper protocols because of systemic barriers. There is an acute need for concrete institutional actions regarding the development of safety policies, adequate resources, and specialised instructors, which would reduce the gap between the perception and actual conditions on the ground.
Keywords: Punjab; Sports safety; institutional aid; perception of safety; physical education; prevention of injuries; safety policies; university lecturers